Pengaruh Corporate Image dan Persepsi Mahasiswa terhadap Minat Menabung di Bank Syariah (Studi Kasus Pada Mahasiswa Universitas Islam Negeri Raden Intan Lampung) - Putri Imaniar; Muhammad Iqbal Fasa; Suharto Suharto (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2021)
The purpose of this study was to determine the effect of the corporate image and perceptions of students at Islamic State University's Raden Intan Lampung on the interest in saving at Islamic banks. The research method used is descriptive quantitative research with multiple linear regression analysis techniques. The data sources used in this study are primary data collected from the results of the respondents' responses according to the questionnaire that was given to 35 people. The results showed that the variables of corporate image and perception had a significant positive effect in part and at the same time on the interest in savings in Islamic banks. The results of this study provide a reference to Islamic banks, that the image and perceptions of the company influence the interest in saving, so Islamic banks should continue to disseminate information to the public.